2021
DOI: 10.3390/coatings11030367
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Fusarium oxysporum Tomato Fruit Rot under Tropical Condition Using Both Chitosan and Vanillin

Abstract: Tomato Lycopersicon esculentum Mill. is one of the most cultivated and widely consumed vegetables in the world. However, it is very susceptible to the infection initiated by Fusariumoxysporum fruit rot, which shortens post-harvest life and thus reduces market value. This disease can be regulated appropriately by the application of synthetic fungicides. However, chemical fungicides constitute a serious health risk, and have harmful environment effects and increase disease resistance, even when microbes are dead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 62 publications
0
29
0
Order By: Relevance
“…Furthermore, A. alternata becomes aggressive when the fruit develops injury or becomes debilitated during prolonged storage. Environmental factors have been shown to play crucial role in the development of fungal pathogens in fruits (Davari et al, 2020;Safari et al, 2021). Among these fungal pathogens, tomato fruit rot induced by Alternaria spp.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, A. alternata becomes aggressive when the fruit develops injury or becomes debilitated during prolonged storage. Environmental factors have been shown to play crucial role in the development of fungal pathogens in fruits (Davari et al, 2020;Safari et al, 2021). Among these fungal pathogens, tomato fruit rot induced by Alternaria spp.…”
Section: Introductionmentioning
confidence: 99%
“…POD activity was examined at 470 nm according to the method reported by Cakmak and Marschner (1992), using guaiacol as a substrate. The extraction and determination of the phenylalanine ammonialyase (PAL) were conducted using the method reported by Safari et al (2021). The polyphenol oxidase (PPO) activity was determined using the previously reported method (Li et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Various reports show that edible coatings are effective in reducing the ethylene production in tomato. A study conducted by Safari et al (2021) 2018) also reported that chitosan coating when applied on tomato was effective in lowering the ethylene rate by 41% as compared to uncoated samples during storage of 14 days at 20 • C (RH 85%).…”
Section: Ethylene Productionmentioning
confidence: 96%
“…Tomato is more prone to postharvest fungal as well as bacterial decay because of higher water activity, favorable pH, and nutrient richness that serve as growth factors for microorganisms (Safari et al., 2021). The bacterial spoilage is characterized by appearance of soft and sour rot on the surface of tomato.…”
Section: Overview Of Tomatomentioning
confidence: 99%